2019
DOI: 10.1002/chem.201902203
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Metal–Organic Frameworks for Photo‐/Electrocatalytic CO2 Reduction

Abstract: Considerable attention has been paid to the utilization of CO 2 ,a na bundant carbon source in nature. In this regard, porouscatalysts have been eagerly explored with excellent performance for photo-/electrocatalyticr eduction of CO 2 to high valued products. Metal-organic frameworks (MOFs), featuring large surface area, high porosity,t unable composition and unique structuralc haracteristics, have been widely exploitedi nc atalytic CO 2 reduction. This Minireview first reports the current progress of MOFs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 130 publications
0
20
0
Order By: Relevance
“…Due to the poison of surface reactive sites, the activity of common catalysts degrades with increasing reaction time. [36,37] To date, most catalytic systems for the photoreduction of CO 2 can only operate steadily over periods of several to several tens of h, [4][5][6] and only few catalysts reach around 100 h stability, [16,38] significantly impeding the commercialization of existing catalysts. Herein, the long-term stability of the catalyst was evaluated by comparing NMR, UV/ Vis absorption, and Fourier-transform infrared (FTIR) spectra (Figure S9) of the fresh and the used DTBT-C 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the poison of surface reactive sites, the activity of common catalysts degrades with increasing reaction time. [36,37] To date, most catalytic systems for the photoreduction of CO 2 can only operate steadily over periods of several to several tens of h, [4][5][6] and only few catalysts reach around 100 h stability, [16,38] significantly impeding the commercialization of existing catalysts. Herein, the long-term stability of the catalyst was evaluated by comparing NMR, UV/ Vis absorption, and Fourier-transform infrared (FTIR) spectra (Figure S9) of the fresh and the used DTBT-C 60 .…”
Section: Resultsmentioning
confidence: 99%
“…MOFs are a new type of porous material with metal ions or clusters coordinated with organic ligands. Due to their high porosity, large specific surface area and flexible structure, MOFs have been applied in electrocatalytic research recently [43,132]. However, some disadvantages, such as poor conductivity and less active centers, hamper their electrocatalytic activity.…”
Section: Mof Materialsmentioning
confidence: 99%
“…Therefore, 2D structures can promote the chemisorption of reactants and improve catalytic performance. A large class of 2D materials, such as noble metals, metal oxides, graphene, graphite carbon nitride (g-C 3 N 4 ), transition metal dichalcogenides (TMDs), metal-organic frameworks (MOFs), etc., has been demonstrated to have great potential to catalyze CO 2 conversion reactions [38][39][40][41][42][43]. Particularly, graphene, known as the first invented 2D material, has attracted extensive attention for many applications [44].…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] However, these reviews could not fully cover the representative research achievements of titanium-based MOF from crystal engineering to photocatalysis in the recent years, especially the latest several years, at which time both the structures and photocatalytic applications of Ti-MOFs had made a significant progress. [27,28] Recently, a review about Ti-MOFs and their derived materials for photocatalysis had been reported. [29] This review article focuses on the titanium-based MOFs composites and derived TiO 2 materials for photocatalytic reaction of H 2 production, remediation of organic and inorganic pollutants, and organic transformation reaction.…”
Section: Introductionmentioning
confidence: 99%